2020
DOI: 10.3390/buildings10110207
|View full text |Cite
|
Sign up to set email alerts
|

A Construct Validation Approach for Exploring Sustainability Adoption in Pakistani Construction Projects

Abstract: Sustainable Project Management (SPM) is a novel theme in construction industries of developing countries and very little is known (so far) about the sustainability performance of construction projects in those settings. Accordingly, the quantitative measurement of SPM as a higher-order construct is not well established and lacks a holistic approach and homogenous taxonomy of indicators. This study explores the SPM practices of construction firms by validating SPM as a second-order construct in the Pakistani co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
0
7
0
1
Order By: Relevance
“…In addition, most of the prior studies on SPM and PS were conducted in the developed world context (Carvalho & Rabechini, 2017;Dubois & Silvius, 2020;Goel et al, 2019;Larsson & Larsson, 2020;Martínez-Perales., 2018;Stanitsas et al, 2020;Yazici, 2020) while there is a dearth of empirical research looking at the relationship between SPM and PS in developing countries. With few exceptions (e.g., Malik et al, 2020;Ullah et al, 2020), there is a lack of comprehensive understanding of how sustainability is practiced in the Pakistani project management context and to what extent firms are embracing the SPM approach. Sustainability is an emerging phenomenon in Pakistan and most recent studies revealed that firms are in the early stages of sustainability adoption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most of the prior studies on SPM and PS were conducted in the developed world context (Carvalho & Rabechini, 2017;Dubois & Silvius, 2020;Goel et al, 2019;Larsson & Larsson, 2020;Martínez-Perales., 2018;Stanitsas et al, 2020;Yazici, 2020) while there is a dearth of empirical research looking at the relationship between SPM and PS in developing countries. With few exceptions (e.g., Malik et al, 2020;Ullah et al, 2020), there is a lack of comprehensive understanding of how sustainability is practiced in the Pakistani project management context and to what extent firms are embracing the SPM approach. Sustainability is an emerging phenomenon in Pakistan and most recent studies revealed that firms are in the early stages of sustainability adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmad et al (2021) revealed that sustainability adoption in the Pakistani SME sector is fragmented and in particular, the environmental dimension is the least practiced sustainability aspect in the SME sector. Ullah et al (2020) examined the SPM practices in the construction sector of Pakistan. The results of the study revealed that the environmental dimension is considered an important issue, while social sustainability aspects are mostly ignored by construction companies.…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of innovation and sustainability practices yields a multitude of significant benefits for businesses. These benefits enable organizations to gain a competitive ad-vantage [68], improve the quality of their products and services [22,38], optimize processes, strengthen their strategy, and foster a healthier and more empowered work environment. One of the key benefits highlighted is cost savings, which can be achieved through waste reduction [68] and operational efficiency [38].…”
Section: Benefitsmentioning
confidence: 99%
“…In tandem with sustainability hypothetical, CSR refers to organisational behaviours and strategies that consider stakeholders' interests to balance social, economic and environmental efforts (Aguinis & Glavas, 2012). Given the SOP and CSR conceptualisation involving similar multi-dimensional TBL approaches, scholars and practitioners have been normally considered them interchangeably and complementary (Aguinis & Glavas, 2012;Fassin & Van Rossem, 2009;Ullah et al, 2020). For this study, the multi-dimensional SOP construct is conceptualised as the oil palm cooperative's efforts to execute and implement activities that not only focusing on revenues but also to strike a balance between the environmental, social and economic impacts on the market and society at large (Göran .…”
Section: Theoretical Basis Of Sustainability-oriented Practices (Sop) Constructmentioning
confidence: 99%